Producing Single Cell Protein from Poultry Manure and Evaluation for Broiler Chickens Diets - El-Deek, A.A.; Ghonem, K.M.; Hamdy, Saffa M.; Aser, M.A.; Aljassas, Fahad M.; Osman, M.M. (International Journal of Poultry Science, 2009)
An experiment was run to study the possibility of elimination of uric acid from poultry manure and increasing its nutritive value by using it as a medium for single cell protein (SCP, yeast) production. Dried Poultry Manure (DPM) was collected freshly from battery brooders of broiler chicken house, dried in an oven at 80oC for 48 h, crushed with mill and stored in plastic bags. Seven strains of yeast (Candida utilis, Candida tropicalis, 3 strains of Saccharomyces cerevisae, S. uvarum and Rhodotorula rubra) were tested to hydrolyzed uric acid and produce protein when grown on DPM containing medium. In addition, forty five one-day old commercial broiler chicks were used to determine Total Protein Efficiency (TPE) of raw and treated DPM. The chickens were randomly divided among 3 equal groups of approximately similar initial body weight of three replicates each containing 5 chicks. Another, one hundred and sixty two broiler chickens were allotted to 9 dietary treatments of 3 replicates of 6 chickens each in a randomized complete block design. This experiment aimed to evaluate the nutritive value of the treated DPM. The experimental diets were corn-soybean meal diet in which 3, 6, 9 and 12% treated DPM and untreated DPM were added on the expense of soybean meal protein. Candida utilis offered the highest protein yield (12.7%) and the highest efficiency to hydrolyze uric acid; therefore, it was selected for further study. Shorter growth periods (< 5 days) favor protein yields while longer growth times (>5 days) were concomitant to higher uric acid hydrolysis. The optimum amount for protein production and uric acid hydrolysis under the specified fermentation condition were 2 g /50 ml medium and pH range between 6-7. Inoculum size from 2-8% and medium should be consists only 40 g DPM /l without any salt increased the protein yield and high utilized of uric acid. The chemical analysis of the DPM showed 19.1% Crude Protein (CP), 18.2% ash, 7.9% Crude Fiber (CF), 1.7% Ether Extract (EE) and relatively high uric acid content, 7.2%. Fermentation of DPM increased the CP content from 19.1 to 24.9%, the NPN content decreased from 9.6 to 8.7%, uric acid content decreased from 7.2 to 0.3% and the EE increased from 1.7 to 2.4%. Amino acids of fermented DPM were greatly increased than those of the DPM except for glycine, histidine and tyrosine. Results of TPE assay indicated that chickens fed diet containing treated DPM gained significantly more weight than those given diets containing untreated DPM. Chickens fed treated DPM gained significantly more weight than those given the untreated DPM, throughout the experimental period. In conclusion, yeast treatment for DPM improved its nutritive value, thus it could be included up to 9% in broiler diets without adverse effect on growth performance of broiler chickens up to 4 wks of age.